Desakralisasi Mitos dan Rekayasa Spiritual Pernikahan Jilu dan Lusan Besan Dalam Adat Jawa - M. Burhanuddin Ubaidillah; Faizatul Adawiyyah; Lailatul Zakiya (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2026)
The rapid advancement of digital technology has transformed patterns of social interaction within families, including the increasing prevalence of online gaming among married adults. Excessive online gaming by husbands has emerged as a significant challenge to family resilience, potentially disrupting marital communication, emotional intimacy, and household responsibilities. This study aims to examine the dynamics of family resilience in households where husbands experience online gaming addiction by analyzing patterns of family adaptation and the risk of family disintegration. This research employed a normative juridical approach using library research, drawing upon scholarly literature, legal regulations, and relevant theoretical perspectives concerning family resilience and behavioral addiction. The findings indicate that online gaming addiction does not inevitably lead to family disintegration. Family resilience is influenced by the family's capacity to adapt through effective communication, emotional support, shared commitment, and balanced role distribution. However, persistent addictive behavior characterized by neglect of family obligations, financial irresponsibility, and deteriorating marital interaction significantly increases the likelihood of marital conflict and family breakdown. The study concludes that strengthening family resilience requires not only individual awareness of digital behavior but also collaborative adaptation among family members to maintain marital stability amid the challenges of the digital era.